Establishing Effective Health Care Partnerships with Sexual and Gender Minority Patients: Recommendations for Obstetrician Gynecologists - Cook, Scott C.; Gunter, Kathryn E.; Lopez, Fanny Y. (Seminars in Reproductive Medicine, 2017)
Sexual and gender minority patients have historically experienced high rates of inappropriate and low-quality care, disrespect, and discrimination in health care settings, as well as significant health disparities. Obstetricians and gynecologists can take action on multiple fronts if they wish to improve the quality of care for their sexual and gender minority patients. Examples include improving their relationships with sexual and gender minority patients and family members by purposefully reflecting upon individual and team biases, engendering empathy for sexual and gender minority patients, and creating effective working health care partnerships with them. They can also take steps to improve their cultural competency by improving their knowledge base about sexual orientation and gender identity, using welcoming language and creating health care environments that signal to sexual and gender minority patients that they are welcomed and understood. This article documents multiple suggestions and resources that health care teams can use to improve the health and health care of their sexual and gender minority patients.
Keywords: sexual orientation; gender identity; prejudice; patient–provider interactions; culturally competent care